Factors associated with cognitive performance among Orang Asli’s children aged 2 to 6 years old in Negeri Sembilan, Malaysia - Murtaza, Siti Fatihah (2017)
Young children aged 2 to 6 years old are in crucial period of growth development. Attainment of specific cognition related to concentration and attention is important for them to be prepared to perform well in school later in life. Various factors could influence cognition of the children in multidirectional ways during this crucial period. There is limited study determining cognitive performance of underprivileged children who are living in poverty, especially Orang Asli children. Therefore, this cross-sectional study aimed to determine the factors associated with cognitive performance among Orang Asli children aged 2 to 6 years old in Negeri Sembilan, Malaysia. A total of 269 children (50.9% boys and 49.1% girls) aged 2 to 6 years old (M=4.04, SD=1.21 years) and their mothers from 14 Orang Asli villages in Negeri Sembilan participated in this study. A face-to-face interview was administered on mothers to obtain information on demographic and socioeconomic background, home environment, sanitation and hygiene. A 2-day 24-hour dietary recall and dietary diversity scores were used to measure current nutrient intake of the children. Anthropometric measurements of both children (height and weight) and their mothers (height, weight, and waist circumference) were recorded. Cognitive performance [working memory index (WMI), processing speed index (PSI), cognitive proficiency index (CPI)] was measured using the Wechsler Preschool and Primary Scale of Intelligence (WPPSI) IV instrument including picture memory, zoo location, bug search and cancellation tests. Blood samples of the children were collected by a pediatrician to assess hemoglobin, serum iron, serum ferritin and transferrin of the children. Meanwhile, mother’s hemoglobin level was determined using the HemoCue technique. Stool samples of the children were taken to screen for parasitic infections. Nearly one third of the children were underweight (27.2%) and had stunted growth (35.6%). Majority of the mothers were overweight (29.5%) and obese (32.2%). Two in five (38.3%) of the mothers and one in five (21.7%) of the children were anemic. One third of the children had parasitic infections (35.0%). Almost all of the Orang Asli households (96.3%) experienced varying levels of household food insecurity. Meanwhile, about two in five (43.7%) of the children had a low CPI (≤89 points). One in three (31.6 %) had low WMI (≤89 points) and half (50.0%) of the children had low PSI (≤89 points). Multiple linear regression results in this study showed that higher number of years of child’s education (β=0.236, p=0.015), father’s years of education (β=0.234, p=0.016), higher father’s income (β=0.274, p=0.003), lower weight-for-age (β=-0.262, p=0.002), higher height-for-age (β=0.336, p=0.025), absence of parasitic infections (β=-0.329, p=0.001), higher energy (β=0.212, p=0.004) and fat (β=0.319, p=0.029) intakes were predictors for better WMI. These factors predicted 52.4% of variance in WMI. Higher number of father’s years of education (β=0.306, p=0.005), higher child’s hemoglobin level (β=0.209, p=0.044), more learning materials available at home (β=0.299, p=0.007), and more parental responsivity to the child (β=0.247, p=0.009) predicted better PSI, in which 38.5% of variance in PSI were explained by these factors. In term of CPI, higher number of years of father’s (β=0.236, p=0.026) and child’s education (β=0.217, p=0.035), higher father’s income (β=0.250, p=0.003), increase in birth weight (β=0.215, p=0.043), higher intakes of energy (β=0.408, p=0.006), fat (β=0.474, p=0.011), iron (β=0.598, p=0.001), and calcium (β=0.390, p=0.012), absence of parasite infections (β=-0.325, p=0.004), and more parental responsivity to the child (β=0.280, p=0.008) predicted better CPI. These factors predicted 56.2% of variance in CPI. In conclusion, half of the Orang Asli children in this study had low cognitive performance as well as one third of them had poor nutritional and health status. Their cognitive performance (WMI, PSI, CPI) can be enhanced by improving parental education and income level, providing optimal nutrition specifically with iron, educating parents to provide intellectual environment at home specifically increasing learning materials and parenting skills with periodically deworming parasites and early exposure to preschool education. A holistic approach involving parents, communities and government agencies should be established in order to improve cognitive performance of these disadvantaged children.